2019
DOI: 10.1111/cen.13920
|View full text |Cite
|
Sign up to set email alerts
|

Rates of abnormal aldosterone/renin ratio in African‐origin compared to European‐origin patients: A retrospective study

Abstract: Primary hyperaldosteronism is reported to account for approximately 10% of hypertension depending on the population studied. [1][2][3] The initial screening test is the aldosterone/renin ratio. 4 Traditionally, a positive result has been followed by confirmatory testing; however, the importance of the aldosterone/renin ratio (ARR) has been enhanced by the recent Endocrine Society guideline which states that in the setting of spontaneous hypokalaemia, plasma renin activity or concentration (PRC) below detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Further, increased aldosterone‐to‐renin ratios (ARR) have been demonstrated in black patients in numerous studies globally . A recent study by Ahmed et al demonstrated that 57% of patients of African origin who were screened for PA had elevated ARR, which was associated with a lower likelihood of unilateral adenoma on imaging when compared to patients of European origin.…”
Section: Introductionmentioning
confidence: 99%
“…Further, increased aldosterone‐to‐renin ratios (ARR) have been demonstrated in black patients in numerous studies globally . A recent study by Ahmed et al demonstrated that 57% of patients of African origin who were screened for PA had elevated ARR, which was associated with a lower likelihood of unilateral adenoma on imaging when compared to patients of European origin.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to European immigrants, early arterial stiffening (indicating premature vascular aging independent of BP), has been observed in African Americans but only inconsistently in African origin groups in Europe [1032][1033][1034][1035]. Varying degrees of hyperaldosteronism have been found to raise BP disproportionally in people of SSA, African Caribbean and African American origin, probably via underlying salt-sensitivity [1036,1037]. In a recent diagnostic trial for primary aldosteronism, MATCH, 40% of patients were of African origin compared with <20% in the local population [1038].…”
Section: Gender-affirming Hormone Therapy and Hypertensionmentioning
confidence: 99%
“…14 Other studies have shown higher plasma levels of aldosterone in black people. 15,16 Given these facts, knowing that primary hyperaldosteronism is imputed in the genesis of RH, 6,8 it is reasonable to understand the importance of using aldosterone antagonists in the 17 when demonstrating that treatment with amiloride or spironolactone may provide an additional reduction in blood pressure in blacks already receiving conventional antihypertensive therapy. 17 In the present study, considering those who needed 4 drugs or more, only 49.5% used spironolactone, even without plausible justification for not using it.…”
Section: Discussionmentioning
confidence: 99%